2021
DOI: 10.1111/jfbc.13582
|View full text |Cite
|
Sign up to set email alerts
|

Atractylenolide III predisposes miR‐195‐5p/FGFR1 signaling axis to exert tumor‐suppressive functions in liver cancer

Abstract: Background: Antineoplastic activity of atractylenolide III (ATL) has been reported in several malignant tumors. However, its activity has not been completely clarified in hepatocellular carcinoma (HCC). Herein, anticancer effects and underlying molecular mechanisms of ATL were investigated in HCC cells in vitro.Methods: Cell viability was evaluated by CCK-8 assay. Cell migration and invasion were evaluated using the transwell assay. TUNEL staining was performed to evaluate cell apoptosis. Protein expression wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Complex components and targets limit the exploration of mechanisms in herbal medicines. Although multiple active components of Codonopsis pilosula were proved to have anti-HCC potential [ 15 17 ], the overall mechanism of Codonopsis pilosula is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complex components and targets limit the exploration of mechanisms in herbal medicines. Although multiple active components of Codonopsis pilosula were proved to have anti-HCC potential [ 15 17 ], the overall mechanism of Codonopsis pilosula is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…CPP1a and CPP1c are two water-soluble homogeneous polysaccharides isolated and purified from Codonopsis pilosula , and they could induce HepG2 cell apoptosis by upregulating the ratio of Bax/Bcl-2 and activating caspase-3 [ 16 ]. ATL, a sesquiterpenoid extracted from Codonopsis pilosula , exerts tumor-suppressive functions in liver cancer via the miR-195-5p/FGFR1 signaling axis [ 17 ]. However, Codonopsis pilosula , as a kind of Chinese herb, is often used as a whole in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…AT-III is a Chinese traditional herb with a long medicinal history isolated from the dried rhizome of Atractylodes macrocephala. In recent years, many basic and clinical studies have shown that AT-III has anti-cancer effects ( Ji et al, 2019 ; Bailly, 2021 ; Sheng et al, 2021 ). However, the effects of AT-III on GPL has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Atractylodes macrocephala is one of the traditional Chinese medicinal herbs, which has obvious curative effects on anorexia, dyspepsia and diarrhea ( Wei et al, 2011 ; Zheng et al, 2012 ). Atractylenolide III (AT-III) is the main bioactive component of Atractylodes macrocephala and it has been proved to possess pharmacological properties include anti-inflammatory, antioxidative, anti-tumor and anti-angiogenesis effects ( Hoang et al, 2012 ; Wang et al, 2015 ; Huai and Ding, 2020 ; Bailly, 2021 ; Sheng et al, 2021 ). A previous study demonstrated that AT-III might play a gastroprotective role in ethanol-induced acute gastric ulcer by reducing extracellular matrix damage ( Wang et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Kang et al [ 70 ] determined that ATL III reduces the viability of human lung cancer A549 cells, increases LDH release, induces apoptosis, and has anti-lung cancer effects, possibly by increasing Caspase-3 and Caspase-9 protein expression, activating the mitochondrial pathway, leading to PAPR cleavage. By upregulating miR-195-5p and downregulating FGFR1 expression, ATL III suppresses proliferation and promotes apoptosis in human hepatoma cells HepG2 and SMMC7721 [ 71 ]. Liu et al [ 72 ] discovered that ATL III activates anti-tumor immunity by inhibiting the phosphorylation of Jak3, Stat3, and the nuclear translocation of Stat3, and downregulating the expression of IDO in interferon-γ-induced lung cancer cells, and its interaction site with Jak3 protein is leucine 905.…”
Section: Pharmacological Effects Of Atractylenolidesmentioning
confidence: 99%